Complexation of Eu(iii) with Cucurbit[n]uril, n = 5 and 7: A Thermodynamic and Structural Study1. Issue 9 (7th March 2015) - Rawat, Neetika; Kar, Aishwarya; Bhattacharyya, A.; Rao, Ankita; Nayak, S. K.; Nayak, C.; Jha, S. N.; Bhattacharyya, D.; Tomar, B. S.
<x xml:space="preserve">Abstract</x> An investigation of Eu(iii) CBn complexes in solution using calorimetry, TRFS, EXAFS and DFT calculations shows the presence of Eu(iii) in different binding modes depending on the cavity size of CBn and the stoichiometry of the complex.